Evaluation of kids rearing system for meat production - SHINDE, A K; SINGH, N P; SEN, A R; VERMA, D L (The Indian Journal of Animal Sciences, 2013)
Marwari goats (60; 3-4-years old) were randomly distributed into 3 groups of20 each and maintained under intensive, semi-intensive and extensive system of feeding. The kids born from these animals were also maintained under the 3 respective systems. Birth and slaughter weights (8 month) of kids were found higher under semi-intensive than those were under extensive and intensive systems. Dressing yield on live weight basis was higher in semi-intensive compared to intensive and extensive systems. Intensive feeding with minimum movement increased caul and kidney fat in the kids of intensive than extensive system. Expenditure on rearing of kids including cost of milk suckled, concentrate mixture, green fodder, labour and treatment was higher in intensive (Rs 797/kid) followed by semi-intensive (Rs 521/ kid) and extensive (Rs 416/kid) system. Total receipt from sale of meat produce and manure were higher in semi-intensive (Rs 981/kid) than intensive (Rs 8991kid) and extensive (Rs 855/kid) system. Net profit per kid in intensive, semi-intensive and extensive system was Rs 102,459 and 439 respectively. It can be safely concluded that extensive and semi-intensive system of kid rearing are more remunerative provided adequate grazing lands are available for grazing / browsing of the kids.